2015
DOI: 10.2147/ott.s85272
|View full text |Cite
|
Sign up to set email alerts
|

B7-H3 silencing by RNAi inhibits tumor progression and enhances chemosensitivity in U937 cells

Abstract: BackgroundThe role of B7-H3 in acute monocytic leukemia U937 cells has not been thoroughly investigated.Materials and methodsB7-H3 knockdown in the U937 cell line was performed using small hairpin (sh)RNA lentivirus transduction. The effects on cell proliferation, cycle, migration, and invasion were investigated by Cell Counting Kit-8 assay, methyl cellulose colony-forming assay, propidium iodide staining, and Transwell assays in vitro. Changes in cell growth inhibition and apoptosis, when combined with chemot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…A recent study from Chen et al demonstrated that induced expression of B7-H3 on the lung cancer cells and macrophages suppressed T-cell mediating anti-tumor immune response [29]. Furthermore, it is reported that inhibition of B7-H3 by siRNA significantly suppresses cell migration and invasion, enhances sensitivity to chemotherapeutic drugs in acute monocytic leukemia U937 cells [30]. In pancreatic carcinoma, it is suggested that silencing of B7-H3 increases gemcitabine sensitivity through induction of surviving-dependent apoptosis [31].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from Chen et al demonstrated that induced expression of B7-H3 on the lung cancer cells and macrophages suppressed T-cell mediating anti-tumor immune response [29]. Furthermore, it is reported that inhibition of B7-H3 by siRNA significantly suppresses cell migration and invasion, enhances sensitivity to chemotherapeutic drugs in acute monocytic leukemia U937 cells [30]. In pancreatic carcinoma, it is suggested that silencing of B7-H3 increases gemcitabine sensitivity through induction of surviving-dependent apoptosis [31].…”
Section: Discussionmentioning
confidence: 99%
“…Based on a few preclinical animal studies, the combination of B7-H3 blockade and chemotherapy looks promising ( Figure 1F ). Indeed, the silencing of B7-H3 through shRNA in an histiocytic lymphoma derived human cell line, U937, in combination with the anti-neoplastic drug Ara-C led to 80% tumor reduction compared to the 40% inhibition observed in wild-type U937 cells combined with Ara-C in a mouse xenograft model (58). Similarly, shRNA silencing of B7-H3 in a murine model of breast cancer, combined with the chemotherapeutic Paclitaxel, showed approximately 80% reduction in tumor growth compared to the untreated wild-type cells (38).…”
Section: Clinical-translational Advancesmentioning
confidence: 99%
“…B7‐H3 knockdown by RNA interference in pancreatic cancer as well as gastric cancer decreased tumor cell migration and transwell invasion up to 50% in vitro, as described in Figure . In the context of oral carcinoma, esophageal carcinoma, breast cancer as well as acute monocytic leukemia, knockdown of B7‐H3 suppressed tumor cell proliferation, while restoration of B7‐H3 expression enhanced tumor growth. In addition, silencing of B7‐H3, through lentivirus‐mediated delivery of stable short hairpin RNA, was observed to increase the sensitivity of the human pancreatic carcinoma cell line Patu8988 to gemcitabine as a result of enhanced drug‐induced apoptosis, indicating that B7‐H3 induces gemcitabine resistance in pancreatic carcinoma cells .…”
Section: B7‐h3 In Cancer Immunotherapymentioning
confidence: 99%